2005
DOI: 10.1002/app.21808
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of high‐ortho‐substitution phenol–formaldehyde resins

Abstract: ABSTRACT:The relationship between the use of 19 kinds of metal catalysts and the proportion of ortho-ortho links of novolac resins was studied. The proportion of ortho-ortho links of novolac resins was characterized with Fourier transform infrared, 1 H-NMR, and 13 C-NMR. The effects of different catalysts and different reaction conditions, such as the molar ratio of phenol to formaldehyde, the pH value of the reaction, and the reaction time, were examined. Phenolformaldehyde resins were synthesized with a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 13 publications
5
34
0
1
Order By: Relevance
“…2(a)], which was further confirmed by the appearance of a strong peak at 1.3 d. The terminal methyl group of the alkyl side chain was also seen, as there appeared a small peak at 0.8 d. The peak at 3.7 d indicated the presence of methylene protons of C 6 H 5 ACH 2 AC 6 H 5 for the bridge between the phenyl rings. [25][26][27] All these spectral data indicated that the condensation of methyolated cardanol was completed under the experimental conditions [see Fig. 2(b,c)] and was fully consistent with the proposed structure (Scheme 1) resulting from the reaction mechanism shown in our recent article 16 for the cardanol-based novolac resin prepared with a citric acid catalyst.…”
Section: Ftir Spectroscopic Analysis Of Cf 71 and Cf 72supporting
confidence: 80%
“…2(a)], which was further confirmed by the appearance of a strong peak at 1.3 d. The terminal methyl group of the alkyl side chain was also seen, as there appeared a small peak at 0.8 d. The peak at 3.7 d indicated the presence of methylene protons of C 6 H 5 ACH 2 AC 6 H 5 for the bridge between the phenyl rings. [25][26][27] All these spectral data indicated that the condensation of methyolated cardanol was completed under the experimental conditions [see Fig. 2(b,c)] and was fully consistent with the proposed structure (Scheme 1) resulting from the reaction mechanism shown in our recent article 16 for the cardanol-based novolac resin prepared with a citric acid catalyst.…”
Section: Ftir Spectroscopic Analysis Of Cf 71 and Cf 72supporting
confidence: 80%
“…The 13 C-NMR spectra of all PUF resins are presented in Figure 2. The assignments of the most characteristic chemical shifts are listed in Table 2 based on the former studies and literatures [7,8,[14][15][16][17][18][19]. As can be seen, the spectral features of all PUF resin are qualitatively similar to each other.…”
Section: Chemical Structurementioning
confidence: 57%
“…The reasons were that there were twice as many ortho position of phenolic units available than para position; para-methylol groups reacted more easily with urea units to form methylene bridges, therefore, leading to the para/ortho ratio of methylols less than 1. A bivalent metal ion such as Mg 2+ was reported to be beneficial for increasing the proportion of high-ortho linkage in PF resins due to its ortho-directing effect [14]. For our preparation methods of PUF resin, only co-condensed methylene between phenolic components and urea units were formed and none of self-condensation methylene of phenolic rings was present in all PUF resins.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The terminal methyl group of the alkyl side chain may also be seen as there appeared a small peak at 0.8 d. The peak at 3.7 d indicated the presence of methylene protons of C 6 H 5 ACH 2 AC 6 H 5 for the bridge between the phenyl rings. 30 All these spectral data indicated that the condensation of methylolated cardanol has been completed under experimental conditions and was fully consisted with the proposed mechanism.…”
Section: Resultsmentioning
confidence: 91%